A Feasibility Study on IPILex IPIL-IPIL-Based Disinfectant - Inumerable, Jennifer (College of Engineering, 2003)
This project aims to determine the feasibility of producing an ipil-ipil based disinfectant, and determine its commercial and social profitability. The product aims to offer the Philippine market a viable alternative to synthetic disinfectants with better quality at a lower price. A market study was conducted to determine the existence of a potential market for a disinfectant that is made from ipil-ipil leaves. The name of the product is Ipilex Super: the All-natural, All-around Home Cleaner. Since it is an all-purpose home cleaner, it is more commonly used as a cleaning agent in washing kitchens, appliances, and bathroom tiles. The product however cannot be used on polished wood surfaces. The major users of Ipilex are Philippine households, specifically housewives and mothers. From the market study, it was concluded that the area of concentration would be the households in the National Capital Region. Also the projected demand for Ipilex in years 2004-2008 were also determined, from which the potential market share of the product was estimated. A marketing strategy was also formulated to promote the product effectively. With this the product is expected to be greatly competitive in the industry. The projected sales revenue of the company from the product starts at Php 61,550,676.00 in the first year and increases until Php 142,996,667.54 on its fifth year. Thus, the percentage of the marketing expenses to the sales revenue has an average of 5% for the five year period. With this the introduction of Ipilex to the market is economically feasible. The technical study presented the detailed production process, and the ability of existing local conditions to make the project technically feasible. The machine and manpower requirements for the production were also outlined in the technical part of the study, Several suppliers were evaluated to determine from which should be the raw materials be purchased. The capacity of the production was also determined to be able to produce the estimated required output for each year. A production plan and schedule were designed based on the capacity of the process. Lastly, a facility layout, which satisfies the space requirements of the production and office areas of the company, was presented in the technical study. The said facility will be located in Marikina City. The project's financial feasibility was verified in the financial study through the use of ratios and sensitivity analysis. The financial statements, which include the income statement, cash flow statement, and balance sheet, were presented for the five-year study period. The internal rate of return was determined to be 212.45%. The favorable rate of return will surely attract project investors and selected loaning institutions. Also, from the financial analysis the computed net present value proved that the project is a desirable and acceptable venture. However, a project to be worthy of financing especially from a government institution such as Bank of the Philippine Islands, should not only be concerned with generating profit. It must also be able to provide a considerable amount of benefits to the society. The benefits should outweigh the costs and disbenefits to individuals and the community as a whole; hence, the social profitability study is conducted. In the social profitability analysis, the benefits of the project to the society were enumerated. These include employment, tax contributions to the government and consumer savings in buying Ipilex. Cost benefit analyses were performed to quantify benefits to the market/public, local/municipal government, and the national economy. Indirect benefits and intangibles were also analyzed quantitatively to provide a complete social profitability evaluation for the project. One of the qualitative benefits is the effect of Ipilex on the health consciousness and awareness of Filipinos. It encourages the people to be more conscious and aware of hygienic practices in keeping their surroundings clean. On the other hand, one of the disbenefits of the project is the generation of industrial wastes. However, proper waste management will be implemented to ensure no damage is done to the surroundings. The different socio-economic criteria for the social analysis were also evaluated. These are NPV, IRR and cost-benefit ratio. All these measures yielded positive results. With all the conclusions and decisions made in the different aspects of the study, the production of Ipilex is therefore, feasible.